Assessment of pre-test probability in Primary Health Care using the International Classification of Primary Care - 2 (ICPC-2) - Gustavo Diniz Ferreira Gusso; Paulo Lotufo; Isabela Martins Benseñor (Sociedade Brasileira de Medicina de Família e Comunidade, 2013)
Introduction: The assessment of the patient's reason for encounter using the International Classification of Primary Care (ICPC) is not common in countries without a strong primary health care system. Objective: This study aimed to evaluate the main reasons for encounter and to calculate the pre-test probabilities for frequent problems. Method: A questionnaire was created to study, in each appointment, the reasons for encounter and the clinical problems (or diagnosis). In total, 26 general practitioners of the Family Health Strategy from the municipality of Florianópolis filled the form after appointments, for four weeks over a year. Results: 5,698 encounters were evaluated, with regular distribution among seasons. There were 1,625 reasons for encounter and 1,475 clinical problems per appointment. The 30 most common clinical problems represented 50% of all appointments, covering 13 different chapters of ICPC-2. Patients with fever as symptom had diagnosis of acute upper respiratory infection (37.7%), acute tonsillitis (17.8%) or fever (11%), while patients who received the diagnosis of acute upper respiratory infection had complained of cough (24.2%), fever (22%) or of a throat symptom/complaint (9.8%). Discussion: Episode of care is the best methodology to assess pre-test probability longitudinally. However, it was possible to estimate the pre-test probability by using the data of each encounter, as demonstrated in the case of fever and acute upper respiratory infection, in spite of its follow up limitation, as it was based on encounters. Conclusion: This study shows that plans for continuing professional development should be focused on common symptoms and diagnosis, in order to improve the clinical reasoning guided by studies of pre-test probabilities. Hence, the ICPC-2 as a classification system is a great contribution to transform any health center in a research center, even those in rural areas of low-income countries.